Prospective analysis of pain and pain management in an emergency department - Leigheb, Massimiliano; Sabbatini, Maurizio; Baldrighi, Marco; Hasenboehler, Erik A.; Briacca, Luca; Grassi, Federico; Cannas, Mario; Avanzi, Giancarlo; Castello, Luigi Mario (Acta Biomedica Atenei Parmensis, 2017)
. Background and aim of the work: The aim of pain management in the Emergency Department (ED) is to temporarily optimize patient quality of life by reducing acute discomfort. The goals of this study were to evaluate the intensity and location of pain experienced by patients in the ED, the time to analgesia administration in the ED, and the patient’s satisfaction so to identify potential useful interventions to improve pain management. Methods: We prospectively collected data on the intensity of pain experienced by 137 patients during their ED stays using the Visual Analog Scale (VAS) and the Numeric Rating Scale (NRS). Patients were further stratified by pain intensity according to three categories, and by cause of pain. Results: NRS pain measurements were higher than VAS measurements. Patients who took pain medication within a few hours before their ED visit had a higher mean VAS score at arrival in comparison to patients who did not. Patients treated with pain medications, compared to the non-treated, had more pain at arrival; abdominal pain was treated earlier than non-abdominal pain, whereas no difference in timing of medication administration was noted between traumatic and non-traumatic pain. Among the  hospitalized patients, the chest was the most common location of pain; these patients had lower NRS scores than non-hospitalized patients. Patients with mild to moderate pain were more satisfied then those with severe pain. Conclusions: The discrepancy between NRS and VAS scores suggests that pain intensity cannot be determined accurately according to pain scale data alone but should also incorporate clinical judgment.